(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the duration, in days, of the phenological stages of the ’Xavante’ blackberry cultivated in different volumes of containers and substrates. The duration (in days) of the following phenological stages was evaluated: beginning of flowering bud budding, beginning of flowering, beginning of fruit maturation, beginning of fruit harvest. One dormant bud per stem was also identified for fruit phenology evaluations and the duration (in days) of the following fruit development stages was observed: dormant bud, budding bud, flower bud, partially open flower, open flower, green berry, partially pink berry, pink berry and ripe berry. The ’Xavante’ blackberry cycle from the beginning of bud sprouting to the beginning of harvest ranged between 52 and 56 days in containers with volumes of 10, 20 and 30 liters and in the substrates of coconut fiber and carbonized rice husk. The time elapsed between the flower bud and ripe berry stages was similar in the 10 and 30 liter containers. However, in the volume of 20 liters, the average number of days between the stages was lower. It is concluded that the blackberry cultivar ’Xavante’ shows good adaptability to the coconut fiber substrate, regardless of the container volume. The phenological stages presented, on average, the same number of days, regardless of the substrate and recipient observed.